KORELASI ANTARA KETERSEDIAAN LAPANGAN KERJA, SISTEM PENGUPAHAN DAN PEKERJAAN SEKTOR INFORMAL - Gindo L. Tobing (to-ra, 2015)
Abstract Labor issues in Indonesia is an issue that over the years have always not solved because of the amount of labor in comparison with job availability is not balanced. Besides the problem of limited employment, are compounded by the low wages of workers/laborers in our country. Wage system still uses the term minimum wage is not worth living needs. The informal sector and transmigration may be one solution for the provision of jobs. Kata kunci : Upah dan Pekerja Sektor Informal